2020
DOI: 10.3390/su12156096
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Moringa oleifera Foliage Substituted for Concentrate Feed on Growth, Nutrient Digestibility, Hematological Attributes, and Blood Minerals of Growing Goats under Abu Dhabi Conditions

Abstract: To avoid the depletion and degradation of natural resources and to maintain long-term environmental quality and sustainability, the present study investigated the impacts of Moringa oleifera foliage (MF) as a replacement for concentrate feed on growth performance, blood hematology, serum metabolites, and serum mineral profile in growing goats. A total of 30 growing local goats (4 months old ± 7 days, with an average weight of 15.80 kg ± 147 g), were randomly allotted to five treatment groups comprising 0%, 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
3
4
0
2
Order By: Relevance
“…Moringa seed cake has favorable effect on kidney function parameters by decreasing serum urea and creatinine concentrations. These results are in line with Aboamer et al ( 2020 ) and Zaher et al ( 2020 ), who mentioned that using MSC improves kidney function in ruminants. However, the decrease in urea and creatinine levels can be attributed to the protection of feed proteins from rumen degradation and improvement in protein digestion in the intestine (Aboamer et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moringa seed cake has favorable effect on kidney function parameters by decreasing serum urea and creatinine concentrations. These results are in line with Aboamer et al ( 2020 ) and Zaher et al ( 2020 ), who mentioned that using MSC improves kidney function in ruminants. However, the decrease in urea and creatinine levels can be attributed to the protection of feed proteins from rumen degradation and improvement in protein digestion in the intestine (Aboamer et al 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the decrease in urea and creatinine levels can be attributed to the protection of feed proteins from rumen degradation and improvement in protein digestion in the intestine (Aboamer et al 2020 ). The current results of liver enzymes (ALT and AST) were supported by Zaher et al ( 2020 ), who pointed out that MSC decreased serum ALT and AST concentrations because of its vitamin, flavonoid, glucosinolate, and phenolic acid contents. These components improve antioxidant and anti-inflammatory influences (Ndukaku et al 2015 ) and biological activities (Atta et al 2018 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Feces were collected from each animal, dried in the oven at 60°C for 24 h, and stored for laboratory analysis. The apparent coefficients of crude protein and acid detergent fiber digestibility were determined using a direct method ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…White blood cells are a major component of the body's immune system (Ajith et al, 2017). Zaher et al (2020) reported, replacing daily concentrate feed with M. oleifera leaves to a level of 100% do not affect the blood hematologic profile of growing goats, although replacement starting at a level of 50% reduces feed intake.…”
Section: Feeding Experimentsmentioning
confidence: 99%